PERBEDAAN KEMANDIRIAN ANAK DITINJAU DARI SUBYEK PENGASUHAN ORANGTUA DAN KAKEK-NENEK PADA ANAK USIA 5-6 TAHUN - Rin Rin Fauziah; Ratih Kusumawardani; Kristiana Maryani (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2018)
Independence is the ability to direct and control the feelings of oneself in thinking and acting, responsible, confident, and disciplined. Parenting is a parenting method and parenting method of dealing with children with the goal of shaping character, personality, and giving values for children to be able to adjust to the environment. The purpose of this study was to determine the difference of children independence in terms of parenting and grandparents of children aged 5-6 years in Rangkasbitung East Lebak Banten. This research uses quantitative method with comparative research type, that is research compare between two or more groups in one variable. The population of 9 PAUDs in East Rangkasbitung Village is taken 4 PAUD as sample. From each PAUD taken 20 children who qualify as a sample, obtained 80 children from 4 early childhood consisting of 40 children who are raised by parents and 40 children are raised by grandparents. Data collection techniques used in this study is a questionnaire (questionnaire). The results showed that there are differences in children independence in terms of parenting and grandparents who can be seen from the analysis that is t count> t table (2.045> 1,990) and because sig <0,05 (0,044 <0,05), then H0 is rejected which means there is a significant difference in the independence of children in terms of parenting and grandparents parenting is the independence of children raised by parents higher than children cared for by grandparents. This can be seen from the calculation of the mean value of 123.55 for the independence of children raised by parents and 116.02 for the independence of children cared for by grandparents.